The effect of acupressure therapy on morning sickness in pregnant women at the Berohol health center in Tebing Tinggi city in 2022 - handayani, Purnama (Jurnal EduHealth, 2024)
Morning Sickness is a problem that often occurs in pregnant women. One alternative that can be given to reduce morning sickness is acupressure therapy. This study aims to determine whether there is an effect of acupressure therapy on morning sickness in pregnant women at the Berohol Health Center in 2022. This research is a quasi-experimental study with a one-group pretest-posttest design approach. This research was conducted from September 12, 2022 to September 24, 2022. The population is 32 people. Sampling using purposive sampling with a total sample of 26 people. The results showed that the majority of the incidence of morning sickness before being given acupressure therapy to pregnant women at the Berohol Health Center in 2022 was moderate and the majority of the incidence of morning sickness after being given acupressure therapy to pregnant women at the Berohol Health Center in 2022. Based on the results of the paired t test, it was found that the p value = 0.001 <0.05. The conclusion in this study is that there is an effect of acupressure therapy on morning sickness in pregnant women at the Berohol Health Center in 2022. The suggestion in this study is that the Berohol Health Center makes an alternative to giving acupressure therapy to reduce morning sickness in addition to getting antiemetic drugs from the health center.